Indonesian Religious Culture and the Undercurrent - Gautam Kumar (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2016)
Indonesia is known to the world not only for its unity in diversity outlook but its unique cultural legacy which is being nurtured by its people barring from all faiths and beliefs.  The paper would analyse the historical perspective to focus on the present Indonesian cultural heritage including descriptive analysis as how traditions of Indian Ramayana and Mahabharata and related folklores are carried out on the Indonesian archipelago, and it will analyse as how Indonesian government’s patronage to this unique cultural traditions has made possible to preserve these inexpensive traditions which not only adorn the general mass a unique identity but it gives them a strong feeling of belonging to a common culture.  The study establishes India’s eastern part’s (i.e. Bihar, Orissa, Assam and Bengal) strong cultural links with Indonesia by providing evidences of deep route of oral traditions of Hindu mythological epics in Indonesia i.e. Ramayana and Mahabharata puppetry and dance forms which run on the similar pattern of Ramleela in Bihar and north India in general.   The paper would delve into  various nuances of Indonesian culture, traditions, local languages which were impacted by Indic religions, culture, society and trade.